Positive Trends in FIRE Hint at Protection from Reperfusion Injury - Jacobson, Anne (MD Conference Express, 2008)
FX06, a fibrin-derived peptide, may reduce myocardial necrosis that is associated with successfully reperfused acute ST-segment elevation myocardial infarction, according to results from the FX06 In Reperfusion [FIRE] trial. The FIRE trial showed only modest trends in favor of FX06 but suggests possible protection from reperfusion injury.